Interdental Cleaning and Oral Health Status in an Adult Cohort, 2015 to 2018. (September 2020) - Chaffee, B.W.; Persai, D.; Vora, M.V.
Interdental cleaning is routinely recommended, despite limited evidence supporting efficacy to prevent advanced oral disease endpoints, such as caries and periodontal disease. We aimed to examine associations between interdental cleaning and oral health in a large, generalizable prospective cohort of adults in the United States. Data were drawn from wave 3 (2015 to 2016, n = 26, 086 included in analysis) and wave 4 (2016 to 2018, n = 22, 585) of the adult component (age ≥18 y) of the nationally representative Population Assessment of Tobacco and Health Study. Survey-weighted multivariable regression models estimated the associations between wave 3 weekly interdental cleaning frequency and 6 measures of self-reported oral health—overall rating, tooth extractions, gum bleeding, loose teeth, bone loss around teeth, and gum disease—cross-sectionally and prospectively, with adjustment for established periodontal disease risk factors. As compared with no interdental cleaning, interdental cleaning ≥7 times/wk was prospectively associated with greater odds of excellent self-rated oral health (adjusted odds ratio, 1.37; 95% CI, 1.17 to 1.62), lower odds of bleeding gums (adjusted odds ratio, 0.62; 95% CI, 0.54 to 0.70), but not statistically significantly lower odds of other oral health conditions in the following 12 mo. Older age, lower socioeconomic status, diabetes, and cigarette smoking were consistently associated with worse oral health across all outcome measures. Findings were largely robust to alternative model and variable specifications. Interdental cleaning is associated with better perceived oral health and less self-reported gingivitis. Prevention of more advanced disease states was not demonstrated. These findings should be interpreted cautiously given the self-reported nature of the measures and relatively short follow-up period.